Identification and Expression Profiling Analysis of the Cation/Ca2+ Exchanger (CCX) Gene Family: Overexpression of SlCCX1-LIKE Regulates the Leaf Senescence in Tomato Flowering Phase - Li, Jiao; Zhao, Yaran; Chang, Chenliang; Liu, Xin; Jiang, Jing (Frontiers in Genetics, 2021)
Cation gradients in plant cellular compartments are maintained by the synergistic actions of various ion exchangers, pumps, and channels. Cation/Ca2+ exchanger (CCX) is one of the clades of the Ca2+/cation anti-porters super family. Here, five SlCCXs genes were identified in tomato. Sequence analysis indicated that SlCCXs have the conserved motifs as the CCX domain. Analysis of the expression level of each member of tomato CCX gene family under cation (Mg2+, Mn2+, Na+ and Ca2+) treatment was determined by qRT-PCR. Tomato CCX demonstrated different degrees of responding to cation treatment. Changes in SlCCX1-LIKE expression was induced by Mg2+and Mn2+ treatment. Analysis of the expression of SlCCX genes in different tissues demonstrated that constitutive high expression of a few genes, including SlCCX1-LIKE and SlCCX5, indicated their role in tomato organ growth and development. Overexpression of SlCCX1-LIKE dramatically induced leaf senescence. Transcriptome analysis showed that genes related to ROS and several IAA signaling pathways were significantly downregulated, whereas ETH and ABA siganling pathway-related genes were upregulated in overexpression of SlCCX1-LIKE (OE-SlCCX1-LIKE) plants, compared with the wild type (WT). Moreover, overexpression of SlCCX1-LIKE plants accumulated more ROS content but less Mg2+ content. Collectively, the findings of this study provide insights into the base mechanism through which CCXs regulate leaf senescence in tomato.